Toleranz und Stressresistenz in einem mehrdimensionalen Raum: Kommunikationsphänomene - Семеновских, Татьяна Викторовна; Брук, Жанна Юрьевна (International Dialogues on Education Journal, 2016)
Nowadays scientists are increasingly talking about a ‘multi-dimensional’ person and the world. The diversity of religious, philosophical, scientific, inclusive and social systems testifies to this phenomenon. By individuals’ multi-dimensional space we mean, first of all, their life, their cognition of the world and themselves, as well as heterogeneous and multi-dimensional traditions, culture and art. The notion can cover the multidimensionality of the individual’s body, including his or her mind and psyche. The article deals with the problem of increasing stressors that determine extreme life situations and require an individual’s psychological resilience, which in turn allows us to examine such concepts as tolerance and stress resilience. Tolerance is seen as a positive personal characteristic; a component of social maturity aimed at a dialogical perception of the world. The level of tolerance is determined by the individual’s system of values, reflecting the degree of positive attitude toward the diversity of the world, its social, cultural, ethnic and ideological differences. The relationship between the stress resistance indicators (neuro-psychological stability assessment; ‘Perceptual evaluation of stress resilience type’ by N.P. Fetiskina) and tolerance (tolerance questionnaire by V.S. Magoon, M.S. Zhamkochyan, M.M. Magura; express questionnaire ‘Tolerance index’ by H.W. Soldatova, O.A. Kravtsova, O.E. Khukhlaeva, L.A. Shaygerova) is set via Pearson’s correlation coefficient. The analysis of 124 boys and girls aged 16-17 (high-school pupils from Tyumen schools in Russia) has shown that if a person is stress resilient, he or she is characterized by a high level of tolerance, and vice versa, if a person is not stress resilient, he or she is characterized by a low level of tolerance. However, a tolerant high-school pupil is not a priori stress resilient. The authors emphasize that internal individual human resources are becoming a promising area of research, where stress resilience is regarded as a predictor of tolerance, but not otherwise.